Advances in Manufacturing Engineering Selected articles from ICMMPE 2019 - Emamian, Seyed Sattar; Awang, Mokhtar; Yusof, Farazila; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book presents selected papers from the 5th International Conference on Mechanical, Manufacturing and Plant Engineering (ICMMPE 2019), held in Kuala Lumpur, Malaysia. It highlights the latest advances in the area, brings together researchers and professionals in the field and provides a valuable platform for exchanging ideas and fostering collaboration. Joining technologies could be change to manufacturing technologies. Addressing real-world problems concerning joining technologies that are at the heart of various manufacturing sectors, the respective papers present the outcomes of the latest experimental and numerical work on problems in soldering, arc welding and solid-state joining technologies.
The effect of composition on CO2 freeze-out and critical locus of binary CO2 -CH4 mixture -- Influence of the Agglomeration Phenomenon on the Recast Surface in PMEDM Environment -- Comparison of the Removal Rate in EDM Based on the Mixed Environment -- Influence of Projectile Penetration on the Multiple-Layered Target Based on Statistical and Numerical Analysis -- Fractal Wear Behaviour of Gear Tooth: A Review -- Finite Element Modelling of Nano Porous Sintered Silver Material -- Creep behaviour and adhesion properties of TiC thin film coating grown by RF Magnetron sputtering.
Keywords: Manufactures; Machinery; Tribology; Corrosion and anti-corrosives.; Coatings; Manufacturing, Machines, Tools, Processes; Machinery and Machine Elements; Tribology, Corrosion and Coatings